Development of Group Counseling: A Guidebook in Lesson Study to Increase Creativity - Umbarini Sari, Ni Ketut Kusuma; Gading, I Ketut; Dharsana, I Ketut (Department of Guidance and Counseling, FIP, Undiksha, 2020)
This study aims to develop and test the acceptability of group counseling handbook development in lesson study to enhance student creativity. This handbook is an instrument for counseling guidance teachers in organizing counseling guidance services in schools. The development procedure in this study follows the 4D development model which is limited only to content validation testing. Five experts and guidance counseling practitioners were involved to assess the feasibility of the guidebook. The instrument used for the assessment consisted of 25 items that referred to the acceptability of the manual. The results of the analysis show that the validation of the expert development group counseling guidebook in the setting of lesson study to improve student creativity has a content validity index (CVI) of 0.94 which means very good or special. Based on these results, the development of group counseling handbooks in the setting of lesson studies to enhance student creativity developed in this study has met the eligibility criteria to be used as an instrument in carrying out counseling guidance services.